Non-linear impact of exchange rate changes on US industrial production - Arash Habibi (Journal of Economic Structures, 2019)
This paper contributes to the literature on the nexus between production and exchange rate in the United States (U.S.) by considering non-linear adjustments of exchange rate effects on industrial production in several sectors of the U.S. economy. We employ a Non-linear Autoregressive Distributed Lags (NARDL) model which is built upon the Solow model. We show that there exists a non-linear relationship between these two variables in some of the MMIGs. We document short-run non-linear effects of exchange rate on production of non-energy materials, durable manufacturing, consumer goods and business equipment. The short-run effects last into the long-run for all the sectors. While exchange rate changes have short-run linear effects on production of electricity in the U.S., there are no effects of exchange rate movements on the production of mining, and energy materials. Moreover, the paper finds misspecification error of the model for the case of durable manufacturing. The existence of non-linearities considering import content of exports, support our hypothesis and conclusions. Further, the factors that influence demand provide justifications for our results.
Keywords: 330; Exchange rates; Production; Non-linear ARDL; Asymmetries